2014
DOI: 10.1007/s13213-014-0977-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacterial endophytes from the roots of Cassia tora L

Abstract: In the present investigation, five endophytic bacterial strains isolated from the roots of Cassia tora L. were identified as Bacillus subtilis, Agrobacterium tumefaciens, Bacillus sp., Pseudomonas putida, and Pseudomonas sp. based on biochemical characteristics as well as 16S rRNA gene sequencing. Isolates were screened for plant growth promoting traits, antibacterial activity, antifungal activity, antibiotic sensitivity, and salinity tolerance. The majority of the endophytic strains produced phytohormone indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Endophytic bacterial isolates were characterized on the basis of colony morphology, biochemical characteristics and molecular phylogeny. The morphological and biochemical characteristics of the isolates were examined according to the Bergey’s manual of determinative Bacteriology (Kumar et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Endophytic bacterial isolates were characterized on the basis of colony morphology, biochemical characteristics and molecular phylogeny. The morphological and biochemical characteristics of the isolates were examined according to the Bergey’s manual of determinative Bacteriology (Kumar et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Antifungal activity: The bacterial isolates producing hydrogen cyanide were tested against Aspergillus niger and Fusarium oxysporium on potato dextrose agar media for fungistatic activity. The 24 hour old bacterial isolates were streaked 1 cm away from the 2 mm of fungal disc placed on media plate and uninoculated plate with fungal disc served as negative control (Kumar et al 2015). Antifungal activity was evaluated by fungal growth inhibition after incubating the plates at 30ºC for 7 days.…”
Section: Determination Of Plant Growth Promoting Traitsmentioning
confidence: 99%
“…The endophytic bacterial isolates reside and multiply in the plants where the environment contains relatively high ionic strength which successively tolerated both the biotic and abiotic factors. Previously many authors reported the endophytic strain which successively tolerated the high salt concentration [36][37][38][39]. In this study the endophytic isolates were able to grown differentially at different salt levels.…”
Section: Discussionmentioning
confidence: 81%
“…Endophytic bacterial isolates were characterized on the basis of biochemical characteristics by Bergey's manual of determinative bacteriology [16] and molecular phylogeny by 16S rRNA gene sequencing. Genomic DNA was isolated using GeneiPure TM bacterial DNA purification kit (Bangaluru, India) following the manufacture's protocol.…”
Section: Characterization Of Bacterial Isolatesmentioning
confidence: 99%